1993
DOI: 10.1063/1.354526
|View full text |Cite
|
Sign up to set email alerts
|

Angular distributions of current density in liquid Ga-ion sources

Abstract: Current-voltage (I-V) characteristics and angular distribution of the current density of a liquid gallium ion source were investigated under various emitting tip temperatures and surface flow impedances. It is shown that the I-V slope is significantly influenced by the flow impedance of the liquid gallium on the emitting tip. The slopes of the I-V curve are shown to be steep for an emitting tip with a rough surface, and gentle for a smooth surface. The angular distribution of Ga ions was determined by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similar tendencies were observed in a previous report. 10) Figure 6 is a measurement of the beam stability. It is observed that the beam emission is quite stable; I rms =I avg is less than 1.8% for 4000 s. This (new model) stability is much better than that of the existing structure (old model, Fig.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar tendencies were observed in a previous report. 10) Figure 6 is a measurement of the beam stability. It is observed that the beam emission is quite stable; I rms =I avg is less than 1.8% for 4000 s. This (new model) stability is much better than that of the existing structure (old model, Fig.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The slope of the I-V characteristic curve is critically affected by the smoothness of the tungsten emission surface, i.e., the surface impedance. 10) If the resistance is too small, then the protrusion surface does not form properly, which may cause the beam to be unstable. The pointing procedure, prior to the blunting, etches the wire end acutely.…”
Section: Experimental Methodsmentioning
confidence: 99%